Efficacy of Intraoperative Intervention Following Transcranial Motor-evoked Potentials Alert During Posterior Decompression and Fusion Surgery for Thoracic Ossification of the Posterior Longitudinal Ligament: A Prospective Multicenter Study of the Monitoring Committee of the Japanese Society for Spine Surgery and Related Research. Issue 4 (15th February 2021) - Kobayashi, Kazuyoshi; Imagama, Shiro; Yoshida, Go; Ando, Muneharu; Kawabata, Shigenori; Yamada, Kei; Kanchiku, Tsukasa; Fujiwara, Yasushi; Taniguchi, Shinichirou; Iwasaki, Hiroshi; Tadokoro, Nobuaki; Takahashi, Masahito; et al.
Abstract : Study Design: Prospective, multicenter, observational study. Objective: The aim of this study was to investigate the efficacy of intervention after an alert in intraoperative neurophysiological monitoring (IONM) using transcranial motor-evoked potentials (Tc-MEPs) during surgery for thoracic ossification of the posterior longitudinal ligament (T-OPLL). Summary of Background Data: T-OPLL is commonly treated with posterior decompression and fusion with instrumentation. IONM using Tc-MEPs during surgery reduces the risk of neurological complications. Methods: The subjects were 79 patients with a Tc-MEP alert during posterior decompression and fusion surgery for T-OPLL. Preoperative muscle strength (manual muscle testing [MMT]), waveform derivation rate at the start of surgery (baseline), intraoperative waveform changes; and postoperative motor paralysis were examined. A reduction in MMT score of ≥1 on the day after surgery was classified as worsened postoperative motor deficit. An alert was defined as a decrease in Tc-MEP waveform amplitude of ≥70% from baseline. Alerts were recorded at key times during surgery. Results: The patients (35 males, 44 females; age 54.6 years) had OPLL at T1-4 (n = 27, 34%), T5-8 (n = 50, 63%), and T9-12 (n = 16, 20%). The preoperative status included sensory deficit (n = 67, 85%), motor deficit (MMT ⩽4) (n = 59, 75%), and nonambulatory (n = 26, 33%). At baseline, 76 cases (96%) had a detectable Tc-MEP waveform for at least one muscle, and the abductor hallucis had the highest rate of baseline waveform detection (n = 66, 84%). Tc-MEP alerts occurred during decompression (n = 47, 60%), exposure (n = 13, 16%), rodding (n = 5, 6%), pedicle screw insertion (n = 4, 5%), posture change (n = 4, 5%), dekyphosis (n = 2, 3%), and other procedures (n = 4, 5%). After intraoperative intervention, the rescue rate (no postoperative neurological deficit) was 57% (45/79), and rescue cases had a significantly better preoperative ambulatory status and a significantly higher baseline waveform derivation rate. Conclusion: These results show the efficacy of intraoperative intervention following a Tc-MEP alert for prevention of neurological deficit postoperatively. Level of Evidence: 2 Abstract : A prospective, multicenter study showed that intraoperative intervention after an alert in Transcranial motor-evoked potentials (Tc-MEP) monitoring during surgery for thoracic ossification of the posterior longitudinal ligament can prevent postoperative neurological deficit. Rescue cases (those with no deficit following intervention after a Tc-MEP amplitude decrease of ≥70%) had better preoperative ambulatory status and a higher baseline waveform derivation rate.